Implications of Seismic Velocity Structure at the Junction of Kuril‐Northeastern Japan Arcs on Active Shallow Seismicity and Deep Low‐Frequency Earthquakes. Issue 10 (3rd October 2018) - Shiina, Takahiro; Takahashi, Hiroaki; Okada, Tomomi; Matsuzawa, Toru
Abstract: We estimate the velocity structures of P (Vp) and S waves (Vs) in southern Hokkaido, Japan, where a large number of crustal low‐frequency earthquakes (LFEs) have occurred. To investigate the relationship between structure and crustal seismicity, we compare the obtained velocity heterogeneity between the crustal LFE regions, which are characterized by active volcanoes, Quaternary volcanoes, and seismic swarms. The tomographic results show that low‐velocity zones (LVZs) with high Vp/Vs are located around the Moho discontinuity beneath active volcanoes, and the LVZs extend horizontally from beneath the active volcanoes to other LFE regions. In southern Hokkaido, crustal LFEs also appear inside and below the upper crust as well as around the Moho discontinuity. These intermediate‐depth and deep LFEs are located around the LVZs with a high Vp/Vs ratio, indicating the contribution of partial melt to the LFEs genesis, even at a distance from the active volcanoes. At intermediate depths of the crust, LFEs are distributed even in the high‐velocity zones, adjacent to the LVZs. This indicates that the partial melt migrations within the crust affect the activity of LFE at the intermediate depths. Below the seismic swarms in the upper crust, LVZs with crustal LFEs are distributed, probably owing to upward migrations of fluid originating from the solidification of the partial melt; this indicates a link between the shallow and deep crustal seismicity in southern Hokkaido. Key Points: Constructing detailed P and S wave velocity structures in southern Hokkaido, Japan Partial melt and their movement are related to the genesis of crustal low‐frequency earthquakes Shallow and deep crustal seismicity are linked through fluid and melt migrations